ADMINISTRATION AND FINANCE SYSTEM OF THE OTTOMAN EMPIRE - Meirison Meirison (IAIN Manado, 2020)
The article aims to reveal the form of administration of the Ottoman Empire, which is not much discussed in history books, especially in Indonesia, an administration that seems chaotic. The description and form of administration take from various sources, especially in the collapse and degradation of leadership. The author tries to explain the advantages and disadvantages of the Timar system run by the Ottoman Turkish Empire. Data collection is carried out through literature study, data verification, interpretation, and financial administration chronology writing. The results show that the Ottoman Empire system of government has developed according to its territory-administration of agricultural Land managed by Sipahi and Subasyi. In implementing the Ottoman Islamic Sharia, the judges have the task of settling civil, criminal, and financial cases in coordination with the regional government and the government. At a glance, the Ottoman had a feudal system similar to the West's system at the time, but there were fundamental differences in land ownership. Land tenants in the West have no right to enjoy the harvest, let alone control the Land for generations. Slaves in Western Europe cannot be separated from hereditary Land. They cannot enjoy the agricultural products they have worked for themselves the Timar system's dysfunction results in losses in military, economic, social, and educational procurement. Even though, when analyzed in the Timar system, many support food security. However, this system still illustrates the principle of the land system adopted by Islam, namely Land to the tiller.